Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan PD. Artha Sanggraha Unit Usaha SPBU Shell Fatmawati Jakarta Selatan - Annisa Salzabila; Ratnawaty Marginingsih (Pusat Riset dan Inovasi Nasional, 2024)
Human resources are central and important in shaping the achievement of goals in a company. Factors that affect employee performance include work discipline and work motivation. This research was conducted at PD Artha Sanggraha Shell Gas Station Business Unit Fatmawati, South Jakarta. The study aims to determine the effect of work discipline on employee performance, and work motivation on employee performance. This research uses a quantitative descriptive method and is conducted by observation, questionnaire and interview methods. From the results of the study, it shows that work discipline on employee performance is known to have a significant value of 0.00 <0.05, it is known that the t count value is 6.349> t table 1.67655 and a significant value of 0.00 <0.05 the hypothesis is stated to have a significant effect between work discipline on employee performance. From the results of the study, it shows that work motivation on employee performance is known to have a significant value of 0.00 <0.05, it is known that the value of t count 4.598> t tabel 1.67655 and a significant value of 0.00 <0.05 the hypothesis is stated to have a significant effect between work motivation on employee performance. From the results of the study, it shows that work discipline and work motivation on employee performance are known to be 0.00 < 0.05 and the value of F count 248.294 > F tabel 3.187 with a significant 0.00> 0.05, this statement means that all independent variables of work discipline and work motivation together affect the dependent variable of employee performance is accepted.